Small molecule ectonucleotide pyrophosphatase/phosphodiesterase 1 inhibitors in cancer immunotherapy for harnessing innate immunity - Choi, Junwon (Bulletin of the Korean Chemical Society, 2023)
Ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) was recently identified as a major hydrolase of an endogenous stimulator of interferon genes (STING) agonist, 2′,3′-cyclic guanosine monophosphate–adenosine monophosphate (cGAMP). ENPP1 is a promising therapeutic target in cancer immunotherapy, in which the inhibition of ENPP1 enhances anticancer immunity via STING-mediated innate immune activation. This review highlights the role of ENPP1 in innate immunity and the recent discovery of small molecule ENPP1 inhibitors as immunomodulators in cancer immunotherapy.
Keywords: Adenosine monophosphate; Cancer immunotherapy; Cyclic guanosine monophosphate–adenosine monophosphate; Ectonucleotide pyrophosphatase/phosphodiesterase 1; Ectonucleotide pyrophosphatase/phosphodiesterase 1 inhibitor; Guanosines; Innate immunity; Monophosphates; Phosphodiesterases; Pyrophosphatases; Stimulator of interferon gene; cancer immunotherapy; cGAMP; ENPP1; ENPP1 inhibitor; innate immunity; STING